Antioxidant Capacity, Cytotoxicity, and Acute Oral Toxicity of Gynura bicolor. (4th December 2013) - Teoh, Wuen Yew; Sim, Kae Shin; Moses Richardson, Jaime Stella; Abdul Wahab, Norhanom; Hoe, See Ziau
Abstract : Gynura bicolor (Compositae) which is widely used by the locals as natural remedies in folk medicine has limited scientific studies to ensure its efficacy and nontoxicity. The current study reports the total phenolic content, antioxidant capacity, cytotoxicity, and acute oral toxicity of crude methanol and its fractionated extracts (hexane, ethyl acetate, and water) of G. bicolor leaves. Five human colon cancer cell lines (HT-29, HCT-15, SW480, Caco-2, and HCT 116), one human breast adenocarcinoma cell line (MCF7), and one human normal colon cell line (CCD-18Co) were used to evaluate the cytotoxicity of G. bicolor . The present findings had clearly demonstrated that ethyl acetate extract of G. bicolor with the highest total phenolic content among the extracts showed the strongest antioxidant activity (DPPH radical scavenging assay and metal chelating assay), possessed cytotoxicity, and induced apoptotic and necrotic cell death, especially towards the HCT 116 and HCT-15 colon cancer cells. The acute oral toxicity study indicated that methanol extract of G. bicolor has negligible level of toxicity when administered orally and has been regarded as safe in experimental rats. The findings of the current study clearly established the chemoprevention potential of G. bicolor and thus provide scientific validation on the therapeutic claims of G. bicolor .